Multilingual learning program: pesantren students’ perceptions of the multilingual simultaneous-sequential model - Bin-Tahir, Saidna Zulfiqar; Atmowardoyo, Haryanto; Dollah, Syarifuddin; Rinantanti, Yulini (LPPM Universitas Mercu Buana Yogyakarta, 2017)
This study aimed at determining whether or not the knowledge, educational level, perception, and attitude of the pesantren students affect the implementation of the multilingual simultaneous-sequential model (MSSM). This research employed quantitative research using a survey design. The sample of the study consisted of 100 students of three pesantren schools in the city of Makassar (Pesantren Modern IMMIM, Pondok Madinah, and Pesantren Darul Arqam Muhammadiyah Gombara). The data were collected through the questionnaire and be analyzed descriptively and inferentially using SPSS program. The results found that the knowledge, level of education, perception, and attitude of pesantren students collectively had a positive impact on the MSSM. However, these perceptions have no significant effect on the MSSM implementation partially. The results of this study contributed to developing further multilingual teaching and learning material such as syllabus, lesson plan, and course book for pesantren students in Indonesia, especially in Makassar.